Notes total e híbrida em frangos (Gallus gallus domesticus) como modelo experimental para aves exóticas - Pedrotti, Luís Fernando (2020)
The purpose of this study was to assess the feasibility of the intracloacal hybrid-NOTES (HN) or total-NOTES (TN) techniques in chickens (Gallus gallus domesticus) for biopsy sampling, in two experimental stages: (1) to assess the HN and TN techniques in chicken cadavers for liver and kidney biopsy, regarding the quality of access, complications and general findings; (2) to compare the HN or TN technique for liver biopsy in posture pullets regarding operative time, complications, technical difficulties and histological quality of liver samples. In the first stage of the study, four cadavers of broiler chicken, weighting 2.6 (± 0.7) kg. Both HN and TN surgical approaches for biopsy sampling were performed in all cadavers. Surgical steps were classified into: (1) surgical access, which involved cloacoscopy and endoscope entry into the celomatic cavity. This step was common to both treatments; (2) HN liver and renal biopsy sampling, by insertion of a 5-fr. biopsy forceps through a percutaneous 14G catheter sheath; (3) TN liver and renal biopsy sampling, by insertion of the biopsy forceps through the same cloacal access, in parallel to the endoscope; (4) cloacal synthesis. Both surgical approaches were successfully carried out in all cadavers (n = 4). Time for the surgical steps were 2.7 (± 1.4) min for surgical access, 9.2 (± 3.4) minutes for HN biopsy sampling, 14.6 (± 5.7). min for TN biopsy sampling and 2.2 (± 0.5) min for cloacal incision suture. Besides biopsy sampling, most organs of clinical relevance for avian species were successfully viewed. In the second stage of the study, 12 posture pullets (224.2 ± 16.9g.) were randomly assigned into HN (n = 6) or TN (n = 6) group for liver biopsy. In all animals (n = 12) liver biopsies were successfully carried out. Total surgical time was 33.5 (± 13.7) minutes in the TN group and 32.3 (± 15.8) minutes in the HN group (p = 0.8940). Nine samples presented minimal artifacts and were classified as optimal for histological assessment. In conclusion, both NT and NH transcloacal approaches are feasible for intracoelomatic biopsy sampling in chicken, as an experimental model for exotic avian.